RUSSIA'S POSITION IN THE MULTIPOLAR WORLD AND SERBIA'S STRATEGIC OPTIONS - Proroković, Dušan (Serbian political thought, 2023)
By relying on realistic theories of international relations, using the methods of content analysis, synthesis and comparison, it is possible to monitor and prove the phenomenon of establishing a balance of power in contemporary international relations. One of the key factors in that process is certainly the Russian Federation. The aspiration to redefine the post-Cold War international order and to shape a new one - multipolar and polycentric, is noticeable in Russia's strategies, as well as in the appearances of officials and concrete actions. Undoubtedly, Russia is positioning itself as one of the independent poles in the changing structure of the world political system, which is why it is necessary to consider the strategic options of the Republic of Serbia in that context. The paper consists of five parts. The introductory part is dedicated to the presentation of the framework - methodological and theoretical, as well as key concepts. The second part explains the structure of the world political system and the phenomenon of balance of power, while the third part specifically shows this through the current (foreign policy) positioning of Russia (influence on the transformation of the world political system and balance of power). The fourth part analyzes Russian - Serbian relations, their quality and content, while the fifth part discusses the strategic options of the Republic of Serbia. The time frame of the research is limited to the period from 2008 and the beginning of the global financial-economic crisis until today. For the purposes of the research, contemporary political science, security, economic, legal and historiographical literature was used, as well as primary sources related to decisions of international organizations, institutions of Russia and Serbia, as well as statements of officials relevant to this paper.
Keywords: multipolarity, balance of power, Russia, Serbia, strategic options, modern international relations